Factors Associated With Patient Portal Engagement in Otolaryngology - Jesse K. Siegel; Chloe Verducci; Agnes Hurtuk (OTO Open)
Abstract Objective Online patient portals are important tools for patient engagement, and their use has increased particularly since the COVID‐19 pandemic and the 21st Century Cures Act. However, prior work across various specialties has demonstrated disparities in patient portal usage with respect to age, gender, race, and insurance status. However, this has not been studied in the field of otolaryngology, and not since the onset of the COVID‐19 pandemic. Study Design Retrospective study. Setting Single tertiary care outpatient otolaryngology practice over a 3‐year period (December 2019‐December 2022). Methods We used univariate and multivariate analyses to measure how patient portal use for appointment scheduling varied before and after the COVID‐19 pandemic and across demographic groups including gender, race, age, primary language, insurance type, and primary care physician (PCP) status (Loyola vs non‐Loyola). Results From December 2019 to December 2022, 49,462 unique patients scheduled 221,611 otolaryngology clinic visits. Significantly more online scheduling occurred after the onset of the COVID‐19 pandemic (10.7% vs 1.9%, P < .01). In multivariate analysis, male gender, age <18 or >65 years, non‐English primary language, and outside PCP were all associated with a lower likelihood of online appointment scheduling (P < .01 for each). Patients with Medicare had higher odds of portal use than commercially insured patients when controlling for other demographic variables (P = .034). Conclusion Patient portal use in otolaryngology has markedly increased over the last 3 years, but utilization varies across demographic groups. This provides an opportunity to improve patient portal content and outreach, and ultimately make portals more accessible to diverse patient populations.